Mitochondria-Catalyzed Activation of Anticancer Prodrugs - Raucheisen, Michael; Attia, Dina; Körber, Marlies; Crevillén, Alejandra Aroca; Hidalgo, Andrés; Beierlein, Frank; Imhof, Petra; Mokhir, Andriy (ChemCatChem, 2025)
Mitochondria mediate electron transport chain (ETC) to power ATP synthase. In cancer cells, the ETC is disturbed leading to leakage of electrons that ultimately results in generation of H2O2. This difference between cancer and healthy cells can be used for the design of cancer-specific prodrugs as confirmed in several proof-of-concept studies. Unfortunately, the known prodrugs are either insufficiently cancer cell specific or their activation efficacy is low. In this work, we solved this problem by optimizing the conjugate of a drug camptothecin and a H2O2-responsive aminoferrocene to obtain the prodrug C. The multistep reaction of the prodrug C with H2O2 is >20-fold more efficient than that of the parent system. The prodrug is accumulated and activated in mitochondria of cancer cells in a H2O2-dependent fashion. The anticancer efficacy towards human ovarian cancer A2780 and monocytic leukemia THP1 cells is improved from 573 and >3000 nM (for prodrug B) to 142 and 479 nM (for prodrug C) correspondingly. Additionally to the excellent activity, the new prodrug is not toxic in vivo to a range of blood (red and white blood cells, neutrophils, monocytes, platelets) and bone marrow cells (monocytes, B and T cells and others) in contrast to camptothecin.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Aminoferrocene; Anticancer; Catalysis; Mitochondria; Reactive oxygen species